2005
DOI: 10.1002/ejsp.236
|View full text |Cite
|
Sign up to set email alerts
|

Normativeness and individualism

Abstract: Five experiments were conducted with a twofold aim: firstly, examine the normativeness of some important features of Western individualism, and secondly, determine what aspect of social value serves as the anchor for their potential normativeness. Five key constituents of individualism were studied. A questionnaire composed of five sub-questionnaires was used, each one referring to an 'individualistic' constituent and to its opposing 'collectivistic' referent. Two main paradigms in the judgment-norm approach w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
157
0
17

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(183 citation statements)
references
References 30 publications
(21 reference statements)
9
157
0
17
Order By: Relevance
“…In other words, two judgment norms may differ in the extent to which they are anchored on one or the other dimension of social value (e.g., Dubois, 2005;Dubois & Beauvois, 2005). Our study suggests, however, that these anchors may not necessarily be fixed within a given judgment norm.…”
Section: Discussionmentioning
confidence: 57%
“…In other words, two judgment norms may differ in the extent to which they are anchored on one or the other dimension of social value (e.g., Dubois, 2005;Dubois & Beauvois, 2005). Our study suggests, however, that these anchors may not necessarily be fixed within a given judgment norm.…”
Section: Discussionmentioning
confidence: 57%
“…Even though the primary aim of the present research was not to settle this issue, our study revealed new data favoring the social utility, rather than the social desirability, of PFC. Viewed from this perspective, the social function of consistency may be comparable to that of other constructs that are socially valued in individualistic societies and anchored in social utility dimension, such as an internal locus of control (Dubois, 2003;Jellison & Green, 1981;Perrin & Testé, 2010), self-sufficiency (Beauvois & Dubois, 2005), and belief in a just world (Alves & Correia, 2008, Testé & Perrin, 2013. Future studies are needed to clarify the social value associated with PFC.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using these paradigms have demonstrated the positive social value of internality (Dubois, 2008), individualism (Dubois & Beauvois, 2005), belief in a just world (Alves & Correia, 2008, and ambivalence (Pillaud, Cavazza, & Butera, 2013). What these norms have in common is the fact that they contain ideas that are fundamental for the structures of our modern occidental societies (Beauvois, 2003).…”
Section: The Sociocognitive Approach To Social Normsmentioning
confidence: 99%